Long-Term Outcomes Following Suppressive Antibiotic Therapy: A 10-Year Cohort Study - George, Ruth; Kiss, Christopher; Woolley, Ian; Lau, Jillian S. Y. (Antibiotics (Basel), 2025)
Background: Lifelong antibiotic therapy can be used as a strategy to manage chronic infections deemed incurable. While this may be beneficial in suppressing infections, its long-term consequences remain underexplored. Methods: Conducted at a tertiary healthcare network in Melbourne, Australia, this 10-year longitudinal observational study, starting in 2015, followed up an initial cohort of 29 patients prescribed suppressive long-term antibiotics. Data extracted from medical records included patient demographics, antibiotic use, adverse events, mortality, and Charlson Comorbidity Index scores. Outcomes were assessed using descriptive statistics. Results: Of the original cohort of 29 patients in 2015, 19 were still alive at the five-year follow-up, with 14 of those continuing antibiotic therapy. At the 10-year follow-up, an additional three patients had died (total 11/29; 38%), and one had ceased antibiotics (total 6/29; 21%). Notably, none of the patients who had previously ceased antibiotics resumed therapy. Four patients were lost to follow-up, and only two patients were seen by infectious disease specialists for their long-term antibiotic therapy. Ultimately, of the original 29 patients initially recruited, only seven patients were confirmed to remain on antimicrobials by the 10-year follow-up. Conclusions: This 10-year prospective study highlights the complexities of lifelong antibiotic therapy. While some patients may benefit from prolonged antibiotic therapy with prevention of relapsed infection, the high burden of comorbidities, therapy adjustments, and hospitalizations remains a challenge. Long-term care strategies and individualized treatment approaches are essential. Further research is needed to optimize outcomes and refine criteria for lifelong antibiotic use and its management.